Prevalence of obesity among school children aged between 13 to 15 years at Kecamatan Johan Pahlawan, Kabupaten, Aceh Barat - Sakinah, Harith; Elis Irmawati, .; Mohd Razif, Shahril; Noor Aini, Mohd Yusof (Penerbit Universiti Sultan Zainal Abidin, 2020)
Background: Obesity has reached epidemic levels in developed as well as in developing countries among children and adolescent population. It is known to have a significant impact on both physical and psychological health. However, there is limited published data on the prevalence of obesity among adolescent in each district of Indonesia. Aim & Objective: Thus, this study aimed to investigate the prevalence of obesity among adolescent at Kecamatan Johan Pahlawan, Kabupaten Aceh Barat. Methods: Data collection for socio-demographic characteristics of subjects was conducted by using a questionnaire. Meanwhile, anthropometry data including weight and height were measured using calibrated tools. Body Mass Index (BMI)-for-age z-score was calculated to classify BMI-for-age category of subjects according to gender. The population taken in this study was n=317 subjects. Results: This study found that the overall prevalence of obesity was 18.3%. Overall, 54.6% of subjects had normal weight while overweight accounted for 24.9% of the subjects involved. Only 2.2% of subjects were categorized as underweight. Conclusion: The current study finding showed that the prevalence of obesity among adolescents in Aceh has doubled and much higher as compared to the national prevalence by country and district. Therefore, appropriate action is to be taken to impart community education as well as enriching and reinforcing individual awareness and skills to prevent and manage obesity.